A prática semiótica do meme - Nogueira, Rafael Martins (2021)
This research aims to examine, from a semiotic point of view, the transmedia phenomenon known as meme. The central idea is to describe the functioning of the meme as a semiotic practice, according to the theoretical perspective formulated by the French semiotician Jacques Fontanille, which provides an analysis methodology in which the objects of study are examined at different levels of semiotic relevance but integrated with each other. In the case of this research, the level of semiotic relevance chosen was the level of practices. Despite the large number of works in the field of language and communication studies that take the meme as an object of study, there is little research in the field of discursive semiotics, which justifies this dissertation. Regarding the hypothesis of this work, the practice of the meme takes place in the succession of four enunciative acts: creating, recreating, interacting and sharing, elements that allow systematizing the practice in a syntax capable of contributing to the global understanding of the phenomenon. This hypothesis seems to account for a semiotically oriented description of such a multifaceted and dynamic phenomenon, such as the internet meme. Thus, we test the profitability of the levels of semiotic relevance, while expanding the range of semiotic theory, which is one of the contributions of this work. Thus, when choosing the meme, we not only chose a very current and productive discursive manifestation, but also one that is difficult to grasp, since its definition (in material and in spatial terms) is elusive and constantly changing and migrating. Thus, the choice of the path through practices is a gain in knowledge for meme studies and a good example of the extension of Jacques Fontanille's theoretical proposal.